Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top


It says to next step


Ok, I can do future problems like this, but is there a rule that explains this? What just happened to both sides of the equal sign?

share|cite|improve this question
he preformed two operations simultaneously, consider he multiplied both sides by $x$, then after divided both sides by $13$. Often authors will not explicitly preform every step so keep an eye out for what valid operations you could preform at every stage of a problem. – Deven Ware Sep 14 '11 at 3:21
if my comment helped realize that both answers now explain what I said in more detail so look at them carefully and understand them – Deven Ware Sep 14 '11 at 3:25
up vote 7 down vote accepted

There are two steps here: starting with $$\frac{52}{x}=13$$ we multiply both sides by $x$ to get $$\frac{52}{x}\cdot x=13\cdot x$$ $$52=13\cdot x$$ and then dividing both sides of that by $13$ to get $$\frac{52}{13}=\frac{13\cdot x}{13}$$ $$\frac{52}{13}=x$$

share|cite|improve this answer

For $a, b, c, d$ non-zero,

$\frac{a}{b} = \frac{c}{d}$ is equivalent to

$ad = bc$.

Then if you divide both sides by $c$, you'll get $\frac{ad}{c} = b$

Believe it or not, this is your situation! (with $d = 1$)

share|cite|improve this answer

I'd count several steps here. Anyways...

We start with $$\left(\frac{52}{x}\right)=13$$. Multiplying both sides by x we have $$\left(\left(\frac{52}{x}\right)*{x}\right)=(13*{x}).$$ Since $$\left(\frac{x}{1}\right)=x$$ we have $$\left(\left(\frac{52}{x}\right)*\left(\frac{x}{1}\right)\right)=(13*{x}).$$ Applying the product rule for quotients, we have $$\left(\frac{(52*x)}{(x*1)}\right)=(13*{x}).$$ Since multiplication commutes, we have $$\left(\frac{(x*52)}{(x*1)}\right)=(13*{x}).$$ Applying the product rule for quotients again, we have $$\left(\left(\frac{x}{x}\right)*\left(\frac{52}{1}\right)\right)=(13*{x}).$$ Since $$\left(\frac{x}{x}\right) =\left(\frac{1}{1}\right)$$ we obtain $$\left(\left(\frac{1}{1}\right)*\left(\frac{52}{1}\right)\right)=(13*{x}).$$ Applying the product rule for quotients once again we have $$\left(\frac{(1*52)}{(1*1)}\right)=(13*{x}).$$ Since $(1*1)=1$, and $(1*52)=52$ we obtain $$\left(\frac{52}{1}\right)=(13*{x}).$$ Now we multiply both sides by $$\left(\frac{1}{13}\right)$$ and obtain $$\left(\left(\frac{1}{13}\right)*\left(\frac{52}{1}\right)\right)=\left(\left(\frac{1}{13}\right)*\left(13*{x}\right)\right).$$ Since 13 equals $$\left(\frac{13}{1}\right)$$ we obtain $$\left(\left(\frac{1}{13}\right)*\left(\frac{52}{1}\right)\right)=\left(\frac{1}{13}\right)*\left(\left(\frac{13}{1})*{x}\right)\right).$$ Since * associates we have $$\left(\left(\frac{1}{13}\right)*\left(\frac{52}{1}\right)\right)=\left(\left(\left(\frac{1}{13}\right)*\left(\frac{13}{1}\right)\right)*{x}\right).$$ Applying the product rule for quotients on both sides we obtain $$\left(\frac{(1*52)}{(13*1)}\right)=\left(\left(\frac{(1*13)}{(13*1)}\right)*{x}\right).$$ Since $(1*52)=52$, $(13*1)=13$, and $(1*13)=13$, we obtain $$\left(\frac{52}{13}\right)=\left(\left(\frac{13}{13}\right)*{x}\right).$$ Since $$\left(\frac{13}{13}\right)=1$$ we obtain $$\left(\frac{52}{13}\right)=(1*x).$$ Since $(1*x)=x$, we obtain $$\left(\frac{52}{13}\right)=x$$

Even reasoning in this way steps have gotten left out, such as how we can "multiply both sides by x."

share|cite|improve this answer
Thanks for the edit Zev. From the downvotes it looks like some people don't like this sort of response even if it comes in "standard" notation. – Doug Spoonwood Sep 14 '11 at 12:46

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.